Pengawasan Pemilihan Kepala Daerah Kabupaten Karawang Tahun 2024 - Anjar Nur Syahri; Hanny Purnamasari; Rachmat Ramdani (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
Regional head elections in Indonesia are regulated through Law No. 7 of 2017, PKPU No. 3 of 2022, and Bawaslu Regulation No. 6 of 2024 which is the legal basis for Bawaslu supervision at various levels. This study uses a qualitative approach with a case study method to explore in depth the role of Bawaslu in the Regional Elections, especially in Karawang Regency. Bawaslu together with the District Supervisory Committee supervise all stages, from voter data collection, campaigns, voting, to recapitulation of results. Supervision is carried out through two dimensions: direct and indirect. Direct supervision includes vulnerability mapping, early detection of violations, and field monitoring to ensure the integrity of the election process. Meanwhile, indirect supervision is carried out by public education, inter-institutional coordination, and encouraging community participation. Based on Imron's supervision theory, the role of direct supervision of the Karawang Bawaslu has proven to be crucial in maintaining the credibility, transparency, and integrity of local democracy. On the other hand, indirect supervision strengthens the synergy between Bawaslu, stakeholders, and the community in creating honest, fair, and accountable elections. The combination of these two strategies not only suppresses potential violations, but also strengthens the legitimacy and trust of the public in the results of the 2024 Regional Elections in Karawang.